Analisis Faktor-Faktor yang Mempengaruhi Penerimaan Edukasi Seksual oleh Anak Usia Dini di Lingkungan Sekolah Dasar - Arum Meiranny; Anggie Diniayuningrum; Mufidhatul Khasanah (Journal of Midwifery and Health Science of Sultan Agung, 2024)
The high number of cases of violence in Indonesia, including sexual violence against children, has raised concerns at various levels of society. Lack of sexual education is often the cause of increasing cases of sexual violence, which can damage children's moral aspects and internalization of life norms. This literature review explores the factors that influence the acceptance of sexual education in early childhood by reviewing relevant research articles. The method used was a literature review using references from Google Scholar and PubMed, producing 11 relevant articles, consisting of 7 national articles and 4 international articles. The research results show that effective sexual education requires support from parents, teacher readiness, and adjustments to cultural norms. The results obtained are that acceptance of sexual education is influenced by various factors, including the role of parents, teacher readiness, cultural and social norms and the educational media used. The conclusion is that parents' attitudes and their knowledge play an important role in the acceptance of sexual education programs in schools. Teacher readiness and training as well as the educational media used in delivery also influence the effectiveness of sexual education in elementary schools. In addition, cultural and social norms often act as barriers to implementing these programs.